ANALISIS ASPEK KEPRIBADIAN TOKOH UTAMA DIVA DALAM NOVEL “MUHASABAH CINTA” KARYA DINI FITRIA - Ali Manshur; Muhammad Arif Rahman Hakim (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
Personality is the life of a person as a whole, individually, unique, effort to achieve goals, ability to survive and open up, ability to gain experience. This personality is influenced by the use of the three personality systems in Sigmund Freud's theory, namely the id, ego, and superego. There are three research problem formulations, namely (1) How is the personality aspect related to the main character Diva's id in the novel